Resource recovery for sustainable construction: Strength and microstructure characteristics of municipal solid waste incineration ash as a green alternative to cement in cementitious composites - Saavedra-Flores, E (Elsevier Ltd, 2026)
The building sector is confronted with significant issues related to sustainability due to high carbon emissions and resource consumption from conventional cement production. Additionally, the disposal of municipal solid waste incineration bottom ash (MSWI-BA) poses environmental risks. This study examines the potential of MSWI-BA as partial substitution of cement in cementitious composite formulations, with particular emphasis on its influence on strength and microstructure. The research aims to promote resource recovery, reduce landfill usage, lower carbon emissions, and foster eco-friendly building solutions and efficient waste utilization. Cement was partially replaced with MSWI-BA at substitution levels of 0 %, 10 %, 20 %, and 30 %, and the effects on density, porosity, water absorption, compressive strength, flexural strength, and microstructural characteristics were systematically investigated. Results show a consistent reduction in density and compressive strength with elevating the proportion of MSWI-BA. The compressive strength declined at all ages with higher MSWI-BA levels, showing a 28.49 % loss at 30 % replacement after 28 days. At early age (3 days), the mortar incorporating 10 % MSWI-BA exhibited a modest reduction in flexural performance (13.83 %). However, by 28 days, this mixture surpassed the control matrix with an 8.15 % improvement, reflecting the delayed benefits associated with BA incorporation. In contrast, higher replacement levels (20–30 %) resulted in flexural strength reductions of up to 37 %. Overall, up to 10 % MSWI-BA replacement is optimal for balancing performance and sustainability. Incorporating up to 10 % MSWI-BA as a partial cement replacement supports sustainable construction and circular economy practices without significantly affecting material performance. © 2025 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC license. http://creativecommons.org/licenses/by-nc/4.0/